Addressing the Housing Requirements of Disabled Residents in North-Eastern Poland - Zapotoczna, Marcelina (European Journal of Social Science Education and Research, 2024)
:Since disabled people have lower income and their geographical mobility is lower, they often tolerate inappropriate housing conditions, i.e. conditions that do not suit the type and degree of their disability. This article presents the results of interviews conducted among people affected by various degrees of disability. The main aim of the study was to determine the housing needs in regard to quality and to the extent to which the needs are satisfied by people living in the north-east of Poland. The first stage of the study involved identification of the factors that determine the quality of housing that satisfies the basic needs and barriers which prevent performing everyday activities. Subsequently, a multidimensional analysis was conducted to assess the extent to which the housing needs are satisfied in groups identified by the degree of disability. The synthetic measures and distance-related indexes suggested the existence of large diversity in the level of satisfaction of housing needs in the groups of disabled people under study.
Keywords: housing needs, disabled people, multidimensional analysis